Patterns and Predictors of Compliance in a Prospective Diary Study of Substance Use and Sexual Behavior in a Sample of Young Men Who Have Sex With Men. (June 2018) - Newcomb, Michael E.; Swann, Gregory; Estabrook, Ryne; Corden, Marya; Begale, Mark; Ashbeck, Alan; Mohr, David; Mustanski, Brian
Behavioral diaries are used for observing health-related behaviors prospectively. Little is known about patterns and predictors of diary compliance to better understand differential attrition. An analytic sample of 241 young men who have sex with men (YMSM) from a 2-month diary study of substance use and sexual behavior were randomized to complete daily or weekly timeline followback diaries. Latent class growth analyses were used to analyze data. Weekly and daily diary groups produced similar compliance patterns: high, low, and declining compliance groups. Black YMSM were more likely to be in the declining compared with the high compliance group. YMSM who were randomly assigned to receive automated feedback about risk behaviors did not differ in compliance rate compared with those who did not. Risk behavior engagement did not predict compliance in the daily condition, but some substances predicted compliance in the weekly condition. Implications for observational and behavior change methods are discussed.